Gender construction in the classical fiqh book Masāil al-Nisā’: Analysis from Judith Butler's perspective - Fina Mazida Husna; Indar Wahyuni; Mowafg Masuwd (An-Nisa’ Journal of Gender Studies, 2025)
A major issue in classical fiqh is gender representation, where women are often positioned subordinate to men. Masāil al-Nisā’ constructs female identities and domestic roles through the repetition of socio-religious norms. This study analyzes the construction of gender in Masāil al-Nisā’ using the performativity theory of Judith Butler. It reveals how fiqh legitimizes binary norms, naturalizes masculine authority, and religiously reproduces women’s subordination within domestic and marital hierarchies. Employing a descriptive qualitative-interpretative approach, thematic analysis, and Butler’s gender performativity theory, the research analyzes primary texts and supporting literature to uncover constructions of women’s roles, identities, and subordination in domestic contexts. The study on Masāil al-Nisāʾ finds that women’s access to the public sphere is conditional and necessity-based with unclear moral regulation. Textual prohibitions against imitating the opposite sex reinforce binary gender divisions. Women are positioned as inherently domestic supporters of husbands or fathers with limited public roles. Although balance is emphasized, male authority in final decisions results in concealed gender subordination. This study concludes that Masāil al-Nisāʾ constructs a normative and hierarchical gender framework, conditionally granting women public space while consistently positioning men as the primary authority, thereby producing covert subordination in gender relations based on religious legitimacy. This study enriches Islamic gender studies, critiques the concept of women's nature (kodrat), state ibuism, and promotes critical reading of fiqh texts.